2020
DOI: 10.31649/1997-9266-2020-148-1-13-22
|View full text |Cite
|
Sign up to set email alerts
|

Desulfurization of Industrial Sulfide Alkaline Solutions by Mixed Sorbents

Abstract: Вінницький державний педагогічний університет імені Михайла Коцюбинського; 2 Вінницький національний технічний університет Проаналізовано сучасні методи очищення вуглеводневої сировини (нафта, газ) від сірковмісних сполук (H 2 S, RSН, RSSR, нафтенові кислоти, NaHS, Na 2 S), які ґрунтуються на їхній лужній екстракції з подальшим окисненням киснем повітря на гомогенних або гетерогенних каталізаторах. Не дивлячись на перспективність процесу каталітичного окиснення сірковмісних сполук в технічних розчинах, він має… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
(1 reference statement)
0
3
0
Order By: Relevance
“…Extraction of Cu 2+ -ions (83.2%) from industrial waters of electrochemical copper plating was performed using modified sulfide and hydrosulfide ions of a mixed sorbent (AC + K) [Khudoyavora O. et al 2020c]. Desulfurization of the sulfide-alkaline solutions from S 2-, HS --ions (96.6%) was carried out using a regenerated mixed sorbent (AC + K) [Khudoyarova O. et al 2020a;Khudoyarova O. et al 2020b]. The spent I-40A SN 300 industrial oil, which was used to obtain plastic oils, was regenerated with a mixed sorbent (AC + K) according to the method described in work [Khudoyarova O. et al 2020d].…”
Section: Methodsmentioning
confidence: 99%
“…Extraction of Cu 2+ -ions (83.2%) from industrial waters of electrochemical copper plating was performed using modified sulfide and hydrosulfide ions of a mixed sorbent (AC + K) [Khudoyavora O. et al 2020c]. Desulfurization of the sulfide-alkaline solutions from S 2-, HS --ions (96.6%) was carried out using a regenerated mixed sorbent (AC + K) [Khudoyarova O. et al 2020a;Khudoyarova O. et al 2020b]. The spent I-40A SN 300 industrial oil, which was used to obtain plastic oils, was regenerated with a mixed sorbent (AC + K) according to the method described in work [Khudoyarova O. et al 2020d].…”
Section: Methodsmentioning
confidence: 99%
“…Regeneration of the spent mixed sorbent (AC+K) after the stage of purification of sugar syrup production of soft drinks was carried out according to the method described in works [6,7]. Methods of purification of water-sugar solutions are described in work [7], sulfide-alkaline solutions -in work [8][9][10][11], washing waters of the electrochemical copper plating process -in work [12]. Regeneration of waste industrial oils was carried out according to the method presented in work [13].…”
Section: Methodsmentioning
confidence: 99%
“…To increase the sorption capacity, it is popular to modify the sorption matrix using harmless and available reagents. Analysis of recent research and publications [9][10][11][12]13] has shown that the joint processing and disposal of waste from different industries allows you to remove valuable chemical compounds and significantly improve the ecological condition of the environment in their storage. The complex utilization of industrial waste studied today concerns, first of all, reagent extraction of metal cations from sewage of galvanic productions and other chemical wastes by their interaction and formation of waterinsoluble chemical compounds.…”
Section: Introductionmentioning
confidence: 99%